The endocannabinoid system, a novel and key participant in acupuncture's multiple beneficial effects. (June 2017) - Hu, Bo; Bai, Fuhai; Xiong, Lize; Wang, Qiang
Highlights: Endocannabinoid system (ECS) activation and acupuncture induce similar effects. ECS mediates multiple acupuncture's effects, such as analgesia and neuroprotection. ECS is a novel and key participant in acupuncture's multiple beneficial effects. Acupuncture may produce different beneficial effects via similar key pathways. Findings may enable new techniques which increase the efficacy of acupuncture. Abstract: Acupuncture and its modified forms have been used to treat multiple medical conditions, but whether the diverse effects of acupuncture are intrinsically linked at the cellular and molecular level and how they might be connected have yet to be determined. Recently, an emerging role for the endocannabinoid system (ECS) in the regulation of a variety of physiological/pathological conditions has been identified. Overlap between the biological and therapeutic effects induced by ECS activation and acupuncture has facilitated investigations into the participation of ECS in the acupuncture-induced beneficial effects, which have shed light on the idea that the ECS may be a primary mediator and regulatory factor of acupuncture's beneficial effects. This review seeks to provide a comprehensive summary of the existing literature concerning the role of endocannabinoid signaling in the various effects of acupuncture, and suggests a novel notion that acupuncture may restore homeostasis under different pathological conditions by regulating similar networks of signaling pathways, resulting in the activation of different reaction cascades in specific tissues in response to pathological insults.